Computational river dynamics - Wu, Weiming (Taylor & Francis, 2008)
This comprehensive text on the fundamentals of modeling flow and sediment transport in rivers treats both the physical principles and numerical methods for various degrees of complexity. Included are 1-D, 2-D (both depth- and width-averaged) and 3-D models, as well as the integration and coupling of these models. The volume includes a broad selection of numerical methods for open-channel flows, such as the SIMPLE[copyright] algorithms on staggered and non-staggered grids, the projection method, and the stream function and vorticity method. The state-of-the-art in sediment transport modeling approaches is described, such as non-equilibrium transport models, non-uniform total-load transport models, and semi-coupled and coupled procedures for flow and sediment calculations. Sediment transport theory is discussed and many newly-developed, non-uniform sediment transport formulae are presented.
Keywords: Sediment transport.; Erosion.; elektronické knihy; electronic books